Progressive freeze-concentration of apple juice and its application to produce a new type apple wine. (February 2016) - Miyawaki, Osato; Gunathilake, Mihiri; Omote, Chiaki; Koyanagi, Takashi; Sasaki, Tetsuya; Take, Harumi; Matsuda, Akira; Ishisaki, Kana; Miwa, Syouji; Kitano, Shigeru
Abstract: Progressive freeze-concentration (PFC) by a tubular ice system was successfully applied to concentrate apple juice from 13.7 to 25.5 o Brix under a program controlled operation for the coolant temperature and the circulation pumping speed. The organic acid distribution and the flavor profile analysis revealed that no substantial differences were observed for the juice before and after concentration both in organic acids and flavor components showing the high quality concentration by PFC. This was also confirmed by electronic taste and flavor analyzers. The PFC-concentrated apple juice was fermented to obtain a new type apple wine with alcohol content as high as 13.7 vol-% without chaptalization. The organic acid distribution was slightly changed before and after fermentation while the flavor profile changed drastically. The present technique will be applicable to produce new type of wine from many other fruits. Highlights: Apple juice was concentrated up to 25.5 o Brix by progressive freeze-concentration. Organic acid and flavor profiles were almost completely retained after concentration. Concentrated juice was fermented to obtain apple wine with 13.7 vol-% alcohol.